Fabrication of Mandarin (Citrus reticulate L.) peel essential oil and nano-calcium carbonate incorporated polylactic acid/polyvinylpyrrolidone electrospun webs - Parın, Fatma Nur; Sıcak, Yusuf; Eliuz, Elif; Terzioğlu, Pınar (Igdir University, 2022)
Fibrous materials from polylactic acid (PLA) and polyvinylpyrrolidone (PVP) containing mandarin peel essential oil (MPEO) and/or nano-calcium carbonate were prepared by electrospinning process. The electrospun webs were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and microbiological tests. IR spectra results indicated the existence of interaction among additives and polymer matrix. Obtained SEM results showed that incorporation of essential oil to the polymer matrix have a remarkable effect on the fiber morphology. Essential oil incorporation increased the fiber diameters. The electrospun composite webs were ineffective against Acinetobacter baumannii, Bacillus subtilis, Escherichia coli, Enterococcus fecalis, Klebsiella pneumoniae, Pseudomonas aeruginosa and Staphylococcus aureus.
Keywords: Chemical Engineering; Kimya Mühendisliği